UTILIZATION OF BEEF TALLOW IN THE SYNTHESIS OF ETHYL ESTER NITRATE TO IMPROVE DIESEL OIL - Manga, Joice; Ridhawati, Ridhawati; Damayanti, Jeanne (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
This study aims to test the use of beef fat as a raw material in the manufacture of ethyl ester nitrate, which can be used as an additive to increase the cetane number in diesel oil. In this case, beef fat is converted into biodiesel ethyl ester first through a transesterification reaction process with a mole ratio of beef fat and ethanol of 1: 13 and then converted again into ethyl ester nitrate through a nitration reaction using a homogeneous catalyst of Sulfuric Acid and Nitric Acid reagent. The mole ratio in the nitration reaction between ethyl ester and nitric acid is 1: 1. The ethyl ester nitrate product obtained is then mixed into diesel oil in several concentrations, namely 0.5%; 1% 1.5% and 2%. Then, performance testing is carried out on a diesel engine. The results of the analysis with FTIR show that ethyl ester nitrate has been successfully synthesized from biodiesel ethyl ester. Through performance testing on diesel engines with parameters of engine power (Qtot, kWatt), braking power (BHP, kWatt), fuel consumption (FC, kg/h), specific fuel consumption (SFC, kg/kWh), mean effective pressure (MEP, kPa), and thermal efficiency (ηth) and exhaust emission measurements.